2022
DOI: 10.1111/josi.12533
|View full text |Cite
|
Sign up to set email alerts
|

How COVID‐19 lockdown has impacted the sanitary pads distribution among adolescent girls and women in India

Abstract: This paper empirically explores the impact of COVID‐19 pandemic and its accompanying lockdown on adolescent girls’ and women's access to sanitary pads in India. We have used the National Health Mission's Health Management Information System (NHM‐HMIS) data for the study, which provides data on pads' distribution on a district level. The empirical strategy used in the study exploits the variation of districts into red, orange, and green zones as announced by the Indian Government. To understand how lockdown sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Through the use of highly structured interviews, this study affords insight into how women of different castes experienced fear, loneliness, depression, anxiety, and stress during the COVID‐19 global pandemic. Moreover, government data was uniquely harnessed to understand how menstruating people's access to reproductive hygiene supplies varied with their geographic location within India's level of pandemic lockdown (Babbar et al., 2023).…”
Section: Using Science To Understand How Women's Health and Safety Wa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Through the use of highly structured interviews, this study affords insight into how women of different castes experienced fear, loneliness, depression, anxiety, and stress during the COVID‐19 global pandemic. Moreover, government data was uniquely harnessed to understand how menstruating people's access to reproductive hygiene supplies varied with their geographic location within India's level of pandemic lockdown (Babbar et al., 2023).…”
Section: Using Science To Understand How Women's Health and Safety Wa...mentioning
confidence: 99%
“…For example, a longitudinal study of over 900 people across eight time points concluded that Black women were less likely to trust the COVID‐19 vaccine and were less likely to intend to be vaccinated than were White women, a finding that is particularly concerning given women's increased likelihood to work within spaces that have greater risk of disease exposure (Heiman et al., 2023). Additionally, systematic analysis of government data revealed that women's risk of infection due to decreased access to menstrual hygiene products was related to government‐mandated lockdowns during the coronavirus pandemic in India (Babbar et al., 2023). Multiple structural explanations underlie these findings, including the government not considering menstrual products to be essential items, which caused production and distribution of these hygiene products to be disrupted.…”
Section: Women's Physical Health During the Covid‐19 Global Pandemicmentioning
confidence: 99%
“…Women, in particular, have experienced drastically inequitable consequences resulting from the COVID‐19 pandemic, related to medical care, systemic racial and class disparities, mental health, and motherhood (see Fulcher & Dinella, 2022 ). Importantly, increased unemployment rates have resulted in several negative consequences for impacted individuals and their families, including the inability to pay monthly bills, housing insecurity, food insecurity, essential service loss (e.g., internet services, phone services), loss of childcare, inability to obtain quality healthcare, and the depletion of savings (Babbar et al., 2022 ; Versey, 2022 ).…”
Section: Justice‐involved Mothers: Direct Socioeconomic Impacts Of Co...mentioning
confidence: 99%
“…More recently, empirical research has been published related to the disproportionate impacts of COVID‐19 and its inequalities associated with changes in employment and income, race and ethnicity, gender, parenting, and neighborhood characteristics (Ayoub et al., 2022 ; Dawson et al., 2022 ; Fulcher & Dinella, 2022 ; Garland McKinney et al., 2022 ; Geyton & Johnson, 2022 ; Jiwani et al., 2022 ; Rehbein et al., 2022 ; Versey, 2022 ). Additionally, research has more recently been published concentrating on uniquely vulnerable populations such as women, minorities, low socioeconomic households, and the justice‐involved community (Ayoub et al., 2022; Babbar et al., 2022 ; Dawson et al., 2022 ; Fulcher & Dinella, 2022 ; Garland McKinney et al., 2022 ; Geyton & Johnson, 2022 ; Heiman et al., 2022 ; Ibekwe‐Okafor et al., 2022 ; Jiwani et al., 2022 ; Lipp & Johnson, 2022 ; Rehbein et al., 2022 ; Versey, 2022 ). The present study aims to expand on the current body of literature and understand how neighborhood disorder exacerbates the socioeconomic impacts of the COVID‐19 pandemic, such as employment, housing, and access to basic necessities, particularly while taking into consideration populations especially vulnerable to socioeconomic impacts of the COVID‐19 pandemic: mothers, particularly mothers with justice‐involved sons, women of color, and women of low socioeconomic status.…”
Section: Justice‐involved Mothers: Direct Socioeconomic Impacts Of Co...mentioning
confidence: 99%
“…While the Scottish legislation is welcome, making menstrual health accessible is not just about the provision of affordable period products. The fuller dimensions of period poverty were reported by many countries before the covid-19 pandemic5 and were exacerbated by the lockdowns 567. For example, the pandemic has resulted in increased prices for period products because of supply chain issues, with national shortages reported across Africa,8 Latin America,9 and the US 10…”
mentioning
confidence: 99%